The next-generation Open Targets Platform: reimagined, redesigned, rebuilt. Issue Volume 51:Issue D1(2023) (18th November 2022) - Ochoa, David; Hercules, Andrew; Carmona, Miguel; Suveges, Daniel; Baker, Jarrod; Malangone, Cinzia; Lopez, Irene; Miranda, Alfredo; Cruz-Castillo, Carlos; Fumis, Luca; Bernal-Llinares, Manuel; Tsukanov, Kirill; et al.
Abstract: The Open Targets Platform (https://platform.opentargets.org/ ) is an open source resource to systematically assist drug target identification and prioritisation using publicly available data. Since our last update, we have reimagined, redesigned, and rebuilt the Platform in order to streamline data integration and harmonisation, expand the ways in which users can explore the data, and improve the user experience. The gene–disease causal evidence has been enhanced and expanded to better capture disease causality across rare, common, and somatic diseases. For target and drug annotations, we have incorporated new features that help assess target safety and tractability, including genetic constraint, PROTACtability assessments, and AlphaFold structure predictions. We have also introduced new machine learning applications for knowledge extraction from the published literature, clinical trial information, and drug labels. The new technologies and frameworks introduced since the last update will ease the introduction of new features and the creation of separate instances of the Platform adapted to user requirements. Our new Community forum, expanded training materials, and outreach programme support our users in a range of use cases.